2017
DOI: 10.1016/j.imlet.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The phagocyte respiratory burst: Historical perspectives and recent advances

Abstract: When exposed to certain stimuli, phagocytes (including neutrophils, macrophages and eosinophils) undergo marked changes in the way they handle oxygen. Firstly, their rate of oxygen uptake increases greatly. This is accompanied by (i) the production of large amounts of superoxide and hydrogen peroxide and (ii) the metabolism of large quantities of glucose through the hexose monophosphate shunt. We now know that the oxygen used is not for respiration but for the production of powerful microbiocidal agents downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 114 publications
(113 reference statements)
2
116
0
Order By: Relevance
“…R 2 = 0.9101) [46, 47]. However, phagocytes employ radical generation and pH in signaling and innate effector functions, and therefore we used the glycolytic stress test to isolate glycolytic ECAR from lactate and non-glycolytic ECAR as previously described [4749]. In keeping with our flux analysis, we found that influenza infected DC significantly increased glycolysis resulting in a mean difference of 26.5242 95% CI [1.62, 51.43] (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…R 2 = 0.9101) [46, 47]. However, phagocytes employ radical generation and pH in signaling and innate effector functions, and therefore we used the glycolytic stress test to isolate glycolytic ECAR from lactate and non-glycolytic ECAR as previously described [4749]. In keeping with our flux analysis, we found that influenza infected DC significantly increased glycolysis resulting in a mean difference of 26.5242 95% CI [1.62, 51.43] (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…A hyperactivation of autophagy was observed in human CD11b+ cells upon CCL2 treatment (10). This was shown by detecting an increase in the LC3-II protein (resulting from cleavage off the microtubule-associated protein LC3) that correlates with autophagosome number (199). Together with their other findings of CCL2's influence on cytokine production and macrophage polarization (see CCL2 Induces Context-Specific Macrophage Polarization and Cytokine Secretion), Roca et al suggest that autophagy might play a role in M2 macrophage polarization (10).…”
Section: Activation Of Autophagy Of Monocytesmentioning
confidence: 97%
“…3). Its role in suppressing microbial growth is clear, as humans and mice that lack the enzyme are especially vulnerable to infection (Shiloh et al, 1999;Thomas, 2017). However, it has been surprisingly difficult to figure out exactly how phagocytic ROS production suppresses microbial growth (Slauch, 2011).…”
Section: Ros As An Antimicrobial Weapon Wielded By Phagocytesmentioning
confidence: 99%